Knowledge, attitudes and practices regarding quackery in dentistry at Ayub Dental Hospital, Abbottabad - Aziz, Bakhtawer; Sajjad Khan, Najia; Urooj, Salka; Nazir Qazi, Sidra; Shambleed, Kiran (Journal of the Pakistan Medical Association, 2023)
Objectives: To assess knowledge, attitudes and practices of people regarding dental quackery. Method: The descriptive, knowledge-attitude-practice study was conducted June 2 to August 1, 2022, at the Dentistry Department of Ayub Medical Complex, Abbottabad, Pakistan, and comprised adult subjects of ether gender belonging to lower or middle socioeconomic class and visiting the dental outpatient clinic. Data was collected using a predesigned questionnaire. To explore the subjects’ knowledge, attitude and practice regarding dental quackery. Data was analysed using SPSS 21. Results: Of the 261 subjects. 135(51.7%) were males and 126(48.3%) were females. The overall mean age was 29.15+/-10.15 years. Of the total, 243(93.1%) participants had satisfactory socioeconomic status and 18(6.9%) had unsatisfactory status. There were 97(37.2%) subjects having good knowledge, 217(83.1%) with good attitude, and 53(67.1) showing good practices towards dental quackery. Low socioeconomic status, low awareness, and easy accessibility were the main reasons for people visiting dental quacks. Increasing the number of public hospitals was suggested as the main solution by 119(45.6%) subjects. Conclusion: The level of knowledge, attitude and practice regarding dental quackery was good. Low socioeconomic status and lack of awareness were the two important reasons for quackery. Key Words: Dentistry, Frauds, Healthcare, Malpractice, Quackery.